Giorgio Vasari’s Cupola of Santa Maria del Fiore: The Eye of God - Cheney, Liana De Girolami (Cultural and religious studies, 2021)
In previous studies on the iconographical symbolism revealed in Giorgio Vasari’s fresco decoration for the Cupola of Santa Maria del Fiore (also known as the Dome of Florence, 1572-1574), I discussed three points: (1) the impact of Dante’s Divine Comedy, in particular the Inferno; (2) the influence ofCoppo di Marcovaldo’s mosaic decoration on the cupola of the Florentine Baptistery (1300); and (3) the inspiration of Renaissance Neoplatonism in Vasari’s paintings. (Aspects of this study were published in Cheney, 2016, pp. 488-519; Cheney &Hendrix, 2002, pp. 177-188; Cheney, 1998, pp. 35-55; Cheney, 1987, pp. 1-8). In this essay, I will focus on another iconographical representation: the metaphysical and physical symbolism of the eye ("l’occhio") in Vasari’s cupola imagery (Figure 1). This approach will connect with Cosimo Bartoli’s lecture on Dante’s Divine Comedy and, in particular, on Dante’s Purgatorio (Cantos XXX and XXXI) as well as with Vincenzo Borghini’s program for the decoration of the Cupola of Santa Maria del Fiore.